The Superiority of Surplus: An Interview with Daniel Loick - Tivadar Vervoort; Lietje Bauwens; Daniel Loick (Krisis, 2024)
This interview was conducted in the Summer of 2024 as part of a publishing project about surplus populations and their modes of resistance for the Flemish literary journal nY. Lietje Bauwens and Tivadar Vervoort interviewed Daniel Loick for the occasion of his newest book, Die Überlegenheit der Unterlegenen (Suhrkamp 2024), which discusses a standpoint-theoretical approach to the politics of counter-communities—marginalized social groups that develop better forms of life than those typical of hegemonic social formations.